LITERASI TRANSAKSI ON LINE DALAM PERSPEKTIF SYARIAH: ON LINE TRANSACTION LITERACY IN A SHARIA PERSPECTIVE - Handayani, Yenny Dwi; Amam, Amam; Ibrani, Ewing Yuvisa (Journal Of Human And Education (JAHE), 2025)
This Community Service activity was carried out to provide students with an understanding of online buying and selling from a sharia perspective. It is very important to equip students with an understanding of sharia principles in buying and selling transactions. This activity was carried out using lecture and discussion methods. The lecture method is used to educate students about buying and selling according to sharia principles. Meanwhile, the discussion method is a place for questions and answers about online business based on sharia principles. The expected output targets from this activity are 1) Students are able to understand the process of buying and selling online; 2) Students get information about online buying and selling from a sharia perspective, halal transactions which must not contain maghriblis (maysir, gharar, usury, tadlis). 3) Students who have practiced can develop their business activities according to a sharia perspective. 4) establishment of a sharia financial literacy corner. The results of this service activity are in the form of increasing students' understanding of buying and selling transactions in accordance with a sharia perspective. Evaluation can be carried out by monitoring the location after the community service implementation period is complete. Assistance will continue to be provided in an effort to continue to increase understanding of online transaction literacy from a sharia perspective. The results of this PKM can be seen. The mean value of respondents' answers is 64%, if seen from the interval range it is in the range of 60% - 79.99% so it can be concluded that the respondents' enthusiasm can be said to be "good" in assessing the implementation of the PKM. This indicates that participants in community service activities feel satisfied and that PKM activities are beneficial for the target audience. There are suggestions given by PKM participants so that the same activities can continue with discussion of different topics. Keywords: On Line Shop; Ecommerce; Sharia Principles; Maghriblis